THE PREVENTIVE PRIORITY PLAN BASED ON THE CAUSALITY ANALYSIS OF THE CONSTRUCTION ACCIDENT - Adwitya Bhaskara; Cahyo Dita Saputro; Abul Fida Ismaili; Nia Agustin; Syawaluddin Alim (Construction and Material Journal, 2021)
The case of construction accident that occurred mid-2019 and seized a lot of attention in the surrounding community is a construction accident on the implementation of underpass construction project located in Yogyakarta. The underpass excavation wall in this project collapsed then led two vehicles are fall. Although the types of accidents are almost identical to each project, it does not mean that the same reason causes the accidents. Various methods can carry out efforts to prevent work accidents, one of which is with assessment method and risk analysis using Analytical Hierarchy Process (AHP) which sub indicators are determined using Fault Tree Analysis (FTA). The method conducted with a review in the site by referring to Ministerial Regulation No. 21 year 2019 about the SMKK (Construction Safety Management System) guidelines. This research was conducted to identify the factors and indicators of management of thesupervisory consultant and the contractor. They had a significant influence and contribution to the implementation of the Yogyakarta Kentungan Underpass construction project. The results of this early-stage study served into two outcomes. First, the accuracy of the implementation of construction safety management system based on the assessment of the contractor is 85.938% and the percentage level of accuracy of the supervisory consultant is 97.29%. Both percentages fall into the category of Satisfactory Implementation Assessment because the valuation range is included between 85% to 100%. Second, after analyzing the risk using AHP method, the indicator that is used as a reference priority for the construction safety system of underpass construction projects and has the highest risk level that can causean underpass project construction accident from the contractor's point of view is the sub-indicator of supporting facilities and infrastructure with a risk level value of 0.042 whereas from the supervisory consultant’ perspective is the sub-indicator about to measuring the dimensions of the road building installed in the site with a risk level value of 0.052. Keywords: Assessment, FTA, Causality, Construction Accident, AHP.